A new method to increase the capacity of audio steganography based on the LSB algorithm - Bazyar, Mohsen (Penerbit UTM Press, 2015)
Audio techniques have been developed for audio streaming on the internet. Using the TCP/IP protocol, audio file can be uploaded, downloaded, and transmitted through the internet. This benefit of transmission makes the interest in using audio as cover object in steganography become much stronger. Capacity which is one of the most important properties of audio steganographic methods, evaluates the amount of possible embedding data within the audio file. A new embedding technique of audio steganography is proposed to increase the carrier medium capacity for substitution additional hidden message. With respect to the performed tests, the algorithm succeeds to increase the depth of embedding layer, without having effects on the signal transparency. The maximum number of bits without significant effect on host audio signal for LSB audio steganography is 4 LSBs. The secret message bits are hidden into variable and multiple LSBs layer in this method. Experimental results show that the use of this new technique which apply 7 LSBs for data embedding in comparison the LSB standard algorithm with 4 LSBs improve data hiding capacity of carrier audio by 35% to 55%. It can be observed from listening tests that there is no significant difference between the stego audio acquired from the novel technique and the main signal.